Revisiting Pleiotropic Effects of Type I Interferons: Rationale for Its Prophylactic and Therapeutic Use Against SARS-CoV-2 - Garcia-del-Barco, Diana; Risco-Acevedo, Daniela; Berlanga-Acosta, Jorge; Martos-Benítez, Frank Daniel; Guillén-Nieto, Gerardo (Frontiers in Immunology, 2021)
The pandemic distribution of SARS-CoV-2 together with its particular feature of inactivating the interferon-based endogenous response and accordingly, impairing the innate immunity, has become a challenge for the international scientific and medical community. Fortunately, recombinant interferons as therapeutic products have accumulated a long history of beneficial therapeutic results in the treatment of chronic and acute viral diseases and also in the therapy of some types of cancer. One of the first antiviral treatments during the onset of COVID-19 in China was based on the use of recombinant interferon alfa 2b, so many clinicians began to use it, not only as therapy but also as a prophylactic approach, mainly in medical personnel. At the same time, basic research on interferons provided new insights that have contributed to a much better understanding of how treatment with interferons, initially as antivirals, actually has a much broader pharmacological scope. In this review, we briefly describe interferons, how are they induced in the event of a viral infection, and how they induce signaling after contact with their specific receptor on target cells. Additionally, some of the genes stimulated by type I interferons are described, and how interferon-mediated signaling is torpedoed by coronaviruses and in particular by SARS-CoV-2. Angiotensin converting enzyme 2 (ACE2) gene is one of the interferon response genes. Although for many scientists this fact could result in an adverse effect of interferon treatment in COVID-19 patients, ACE2 expression contributes to the balance of the renin-angiotensin system, which is also greatly affected by SARS-CoV-2 in its internalization into the cell. This manuscript also includes the relationship between type I interferons and neutrophils, NETosis, and interleukin 17. Finally, under the subtitle of "take-home messages", the rationale behind a timely treatment with interferons in the context of COVID-19 is emphasized.